2006
DOI: 10.1159/000095250
|View full text |Cite
|
Sign up to set email alerts
|

Time of Erythema Onset after Application of Methyl Nicotinate Ointments as Response Parameter: Influence of Penetration Kinetics and Enhancing Agents

Abstract: The time of erythema onset may be used as a response parameter for quantification of the cutaneous erythema response induced by methyl nicotinate. The vehicles light mineral oil (LMO; test) and medium chain triglycerides (MCT; standard) were compared with regard to the pharmacodynamic response. Moreover, the influence of penetration enhancers on the time of erythema onset was investigated under zero order penetration kinetics. The enhancers dimethyl sulfoxide, diethylene glycol monoethyl ether and three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…The increased percentage of inadequate anaemia correction when the first dialysis was unplanned is consistent with previous studies showing that the timing of referral to a nephrologist is associated with the quality of pre-dialysis care, including anaemia [22, 23]. In France, only physicians employed on staff in hospitals and dialysis centres, mainly nephrologists, were authorized to prescribe ESA therapy, so that access to these drugs rested as much on timely referral to nephrologists as on nephrologists’ clinical practice.…”
Section: Discussionsupporting
confidence: 88%
“…The increased percentage of inadequate anaemia correction when the first dialysis was unplanned is consistent with previous studies showing that the timing of referral to a nephrologist is associated with the quality of pre-dialysis care, including anaemia [22, 23]. In France, only physicians employed on staff in hospitals and dialysis centres, mainly nephrologists, were authorized to prescribe ESA therapy, so that access to these drugs rested as much on timely referral to nephrologists as on nephrologists’ clinical practice.…”
Section: Discussionsupporting
confidence: 88%
“…The efficacy of a formulation is usually considered to be related to the concentration of active ingredients. For example, higher nicotinate concentrations reduce the time of onset of erythema 14,15 and glucocorticoids may be classified as strong or moderate depending on their concentration in the vehicle. In the present study we found that the efficacy also could be changed by simple modifications of the proportion of water and lipids in the formulation, i.e.…”
Section: Discussionmentioning
confidence: 99%